LEGAL ANALYSIS OF THE DECISION OF THE BANTUL RELIGIOUS COURT IN THE CASE OF DEFAULT AND COMPENSATION IN THE SHARIA ECONOMIC DISPUTE - Rohayatun (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2025)
This research examines the enforcement of legal principles in Sharia economic disputes, particularly focusing on the context of default and compensation in the jurisdiction of the Bantul Religious Court. Given the increasing complexity and volume of Sharia economic disputes, an understanding of how these cases are decided is crucial. There is a gap in the literature regarding the specific application of Sharia principles and law in the Religious Courts in Indonesia, particularly regarding the determination of damages in default cases. This research aims to analyze how the Bantul Religious Court applies relevant legal principles in default cases relating to Sharia economics and to identify the main juridical considerations that influence decisions on the amount and type of damages awarded. Using qualitative legal research methods, this study analyzed court decisions and relevant legal literature to identify patterns and justifications in the court's reasoning. The main findings revealed that the Bantul Religious Court sought to integrate the principles of Islamic law with Indonesian positive law, emphasizing fairness, compliance with sharia principles, and consumer protection. Key considerations include alignment with Sharia, actual losses incurred, the good faith of the debtors, their socio-economic circumstances, and the principles of equity.